CITATION ANALYSIS AND RESEARCH IMPACT OF NATIONAL METALLURGICAL LABORATORY, INDIA DURING 1972- 2007: A CASE STUDY - N. Mishra, Paras; C. Panda, Krushna; G.Goswami, Nani (Malaysian Journal of Library and Information Science, 2010)
This paper provides an insight into the citation analysis of research publications of the National Metallurgical Laboratory (NML) during the period 1972-2007. It analysed 2830 most valuable citations spread over 561 publications made by the NML scientists and researchers indexed in Science Citation Index (SCI) retrieved through the Web of Science. It determines the research and citation impact using parameters such as extent of citation received in terms of number of citation per paper, year wise break up of citation, domain wise citation, self citations and citation by others, diachronous self citation rate, citing authors, citing institutions, highly cited papers and categories of citing documents, citing journals and impact factor. A Bradford plot constructed to determine the core-citing journals shows that the curve is a typical S shape which indicates subject maturity.